應用字本位教學法對提升初級華語學習者漢字與詞彙能力之成效研究 Effectiveness of Applying a Character-Based Teaching Method to Improve the Proficiency of Primary Chinese as a Second Language - 林振興 Zhen-Xing Lin; 王暄博 Hsuan-Po Wang (National Taiwan Normal University, 2019)
不同於拼音書寫系統，漢字視覺組成複雜多變，對以華語作為外語或第二語言之學習者而言，構成極大挑戰。本研究欲以字本位教學法為基礎，涵納第二語言學習的雙碼理論和符合認知心理學的創新記憶術，發展適合華語學習者之策略，以解決漢字難學之學習難點。本研究以菲律賓基督教靈惠學院八年級的華語初級學習者為研究樣本，探討在不同教學法中的學習成效。因此，研究設計在不同教學法中，探討三個研究問題：初始效應、漢字（認讀與書寫）學習成效、詞彙學習成效。經過兩個月的實徵教學研究，結果顯示，接受字本位教學 法之學習者，漢字與詞彙的表現皆優於接受詞本位教學法之學習者；此外，初級學習者的漢字學習成效符合序列位置效果之初始效應理論。 Learning Chinese as a second language (CSL) is difficult because visual characters of Chinese are complicated, and phonetic writing systems are different. The study aimed to develop a learning strategy for overcoming the difficulty in learning Chinese characters for CSL learners by implementing a combination of a character-based learning method and dual code theory of learning a second language with innovative memory based on cognitive psychology. The study targeted primary CSL learners among eighth-grade students of Grace Christian College, Philippines and analyzed the results of different teaching methods. The study investigated three research questions for different teaching methods, including a serial position effect, the effectiveness of learning Chinese characters (reading and writing), and the learning results of vocabulary. After a learning experience of 2 months, the result indicated that the character and vocabulary performance of students who received the character-based teaching method was superior to those who received the word-based teaching method. In addition, the effectiveness of learning Chinese characters among the primary CSL learners was consistent with the theory of the serial position effect.